O banco na internet : um estudo do atendimento em um banco brasileiro - Mello, Roberto Agostinho de (2003)
Aroud the world the companies search for new ways to optimize trading and distribution of theirs own goods and services in order to establish productivity gain and at same time cut costs of production and beat the competition in a dynamic and global market. Aware of the moment the Financial Institutions are among the companies that more invest in automation and Information Technology. The technological transformations implemented in the services arena are changing the performance of the Finantial Institutions and the way they relate commercially with their clients.This work focus analyze the connection between Financial Institutions and their clients usually taking advantage of the options the online banking offers to verify how the clients are responding to the changes. Former studies have showed the concern with automation banking since it didn???t get along in same tune with suitable Customer Service. From these studies a new one had started focusing a retail Brazilian Bank where the advantages, difficulties and lacking in the internet banking are highlighted proving that there are an increasing break up moving away banks and their clients. The result of this work show the need the companies have to improve the knowledge regarding their clients as the only way to have an effective and efficient Customer Service. Also the study details the relevance of history transactions, research, employes out put and suggestions as good informative material and suggests alternatives to develop a good connection that will enrich the needs and respective satisfaction of the clients.